Examining Factors That Can Improve Employee Performance - Dindin Abdurohim; Samuel PD Anantadjaya; Imam Jayanto; Kusdibyo; Pandu Adi Cakranegara (Jurnal Manajemen Bisnis, 2022)
This study aimed to analyze the effect of competence, work motivation, and work environment on employee performance at PT. Bank Mandiri Kartini Makassar Branch with a population of 300 people. With a relatively large population (300 people), the sample was drawn using the Slovin formula so that 75 respondents were obtained. This research is quantitative research where the data source comes from primary data obtained directly from the employees as research respondents using questionnaires and secondary data obtained from decision literature such as books and references related to the material for writing this final project and analysis. documentation from PT. Bank Mandiri (Persero), tbk. The results of this study indicate that partially or simultaneously, the variables of competence, work motivation, and work environment affect positively and significantly the performance of employees at the office of PT. Bank Mandiri Bandung Martadinata.